Ibn al-Jazzar on sexual diseases and their treatment : a critical edition Zād al-musāfir wa-qūt al-ḥāḍir : provision for the traveller and the nourishment of the sedentary book 6 /: a critical edition Zād al-musāfir wa-qūt al-ḥāḍir : provision for the traveller and the nourishment of the sedentary book 6. ([2018?]) - Ibn al-Jazzār
No abstract available